2002
DOI: 10.1088/0264-9381/19/11/311
|View full text |Cite
|
Sign up to set email alerts
|

Dark matter and stable bound states of primordial black holes

Abstract: We present three reasons for the formation of gravitational bound states of primordial black holes, called holeums, in the early universe. Using Newtonian Gravity and nonrelativistic quantum mechanics we find a purely quantum mechanical mass-dependent exclusion property for the nonoverlap of the constituent black holes in a holeum. This ensures that the holeum occupies space just like ordinary matter. A holeum emits only gravitational radiation whose spectrum is an exact analogue of that of a hydrogen atom.A p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(48 citation statements)
references
References 9 publications
1
47
0
Order By: Relevance
“…The suggestion that gravitational quantisation might play a direct role in the solution to the dark matter problem was first made by Ernest (2001) and later using a fundamentally different approach by Chavda and Chavda (2002). In the former case (the approach in this chapter) Ernest considered the effects that the eigenspectral array describing the wavefunctions of traditional particles has on their interaction properties, while Chavda and Chavda consider the bound quantum eigenstate of two micro black holes and suggest that due to their binding, the constituent black holes of such a system will not lose mass in the expected manner (i.e from Hawking radiation).…”
Section: Introductionmentioning
confidence: 99%
“…The suggestion that gravitational quantisation might play a direct role in the solution to the dark matter problem was first made by Ernest (2001) and later using a fundamentally different approach by Chavda and Chavda (2002). In the former case (the approach in this chapter) Ernest considered the effects that the eigenspectral array describing the wavefunctions of traditional particles has on their interaction properties, while Chavda and Chavda consider the bound quantum eigenstate of two micro black holes and suggest that due to their binding, the constituent black holes of such a system will not lose mass in the expected manner (i.e from Hawking radiation).…”
Section: Introductionmentioning
confidence: 99%
“…We proceed then to consider Holeums as a possible origin of certain class of short-lived gamma ray bursts. Holeums are gravitationally bound states created and evolved in the early stages of the big bang (Chavda and Chavda, 2002). We argue that Holeums exhibit a wide range of dynamical properties that make them viable candidates of certain class of short-lived GRBs.…”
Section: Introductionmentioning
confidence: 91%
“…Recently, Chavda and Chavda (2002) have proposed a model of the early universe suggesting the formation of stable quantized gravitational bound states of primordial black holes called Holeum. A segregation property puts the Holeums mainly in the galactic halos where they form an important component of dark matter.…”
Section: Early Universe Quantum Fluctuation and Holeum Theorymentioning
confidence: 99%
“…Chavda & Chavda [73] have shown that PBH in the early universe did not decay until gravity decoupled from other interactions. In this case, they demonstrated that micro PBH, having masses between 8 × 10 18 GeV and 10 19 GeV, formed gravitational bound states called holeums when the temperature of the Universe was between 10 30 K and 10 29 K. Being coupled, these PBH will not evaporate by the Hawking mechanism, unless they are ionized.…”
Section: Primordial Black Holes and Holeumsmentioning
confidence: 99%
“…In other words, the holeum is a gravitational analog of the hydrogen atom. Chavda & Chavda [73] consider holeums as an essential component of DM that populates the Galactic halo. Holeum theory, in spite of its richness, is still in the infant stage, and a lot of future theoretical and observational work has to be accomplished before testing its adequacy as a DM candidate.…”
Section: Primordial Black Holes and Holeumsmentioning
confidence: 99%